Applying Peer Scaffolding to Enhance the EFL Vocational Students’ Speaking Skills - Ince Dian Aprilyani Azir (Ethical Lingua: Journal of Language Teaching and Literature, 2019)
The preliminary study showed that the students at English as a Foreign Language (EFL) in the vocational higher education context found the speaking skills as the most difficult ones to learn. The students also declared that unsupportive English learning atmosphere in the class used to make the students reluctant to speak. This phenomenon also leads the students to have lack of confidence to speak English in the class. Thus, the researcher conducted experimental research using Peer Scaffolding approach using Vygotsky’s theory to check whether it improves the students’ speaking skills. The research involves 156 vocational college students in the second semester of Multimedia Study Program at Politeknik Negeri Media Kreatif Jakarta. After analyzing the data taking from the assessments, interviews, and observation field notes during the study; the findings confirm that the peer scaffolding enhances the speaking skill performances. As the results expose that the peer scaffolding builds the more supportive learning conditions in which the students can give mutual help to improve the speaking exposures, the peer scaffolding is recommended as one of the alternatives to improve the students’ speaking skills.